ANALISIS ETOS KERJA, LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI (Survey Pada Pegawai UPTD Puskesmas Bangkinang Kota) - Zulher, Zulher (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2020)
This study aims to determine the effect of work ethic, work environment and work load on employee job satisfaction at UPTD Puskesmas Bangkinang Kota. Work ethic is a work spirit that is owned by someone to be able to work more in order to obtain value for their lives. The work environment is all the facilities and infrastructure that are around a person who can influence the implementation of their work. Workload is a group or a number of activities that must be completed by an organizational unit or position holder within a certain period of time and job satisfaction is a pleasant or unpleasant situation in which someone views their work. The analysis in this study uses multiple analysis with 64 respondents. Sampling uses the census method, while the hypothesis testing in this study uses the f test and t test. Based on the results of the study it can be concluded that simultaneously and partially, work ethic, environment and workload significantly influence job satisfaction.